Module Development Based on Project Based Learning on the Material Types of Heavy Equipment - Viktorius Fikran Cahaya Gulo; Yelisman Zebua; Envilwan Berkat Harefa; Aprianus Telaumbanua (Universitas Muhammadiyah Enrekang, 2024)
This study concentrates on crafting a module geared towards project-based learning (PBL) centered on heavy equipment material types. Given the increasing demand for adept heavy equipment operators, it is crucial to employ effective educational strategies to impart pertinent knowledge to learners. Commencing with an exhaustive literature review encompassing PBL, heavy equipment operations, and commonly utilized materials in heavy equipment manufacturing, the research proposes a systematic methodology for module development. This approach incorporates pivotal PBL principles like practical problem-solving, collaboration, and inquiry-based learning. The module's design seamlessly blends theoretical underpinnings with hands-on applications, thereby furnishing learners with practical experiences and opportunities for honing critical thinking and skills. Evaluation of the module's effectiveness is conducted through both qualitative and quantitative means, encompassing pre and post-assessments, student feedback, and performance evaluations. The outcomes underscore the module's efficacy in augmenting learners' comprehension of heavy equipment material types and their application in real-world scenarios. This research contributes to the enhancement of educational methodologies in heavy equipment operations by furnishing a structured framework for deploying PBL modules tailored to specific learning objectives.